POLITIK HOKUM PENGAKUAN NEGARA TERHADAP MASYARAKAT HUKUM ADAT DAN HAK-HAK TRADISIONALNYA - Sukirno Sukirno (Masalah-Masalah Hukum, 2011)
The Legal policy of state recognition to the indigenous people during Guided Democracy period, New Order period ( Orde Baru ), until reformation period, carried out carefully by giving four terms as regulated in UUPA, UUD NRJ 1945 and The Act of Fore sty and Plantation Act. So that, the character of the product of the Jaw is not still responsive, because they have not base on to Pancasila ( as a fundamental norm) dan they have not accomodate the aspirations of indigenous peopleand also the International Law instrument. The legal policy of state recognitions to indigenous people in the future need to accomadate indigeneous people's aspirations, International Law instrument which it regulated the indigineous people, and state interest, which it still refferring to Pancasila as 9Jiding principle.